ANALISIS KUALITAS PELAYANAN SURAT TANDA NOMOR KENDARAAN (STNK) DAN PAJAK KENDARAAN BERMOTOR (PKB) PADA KANTOR SAMSAT PALU - Mu’min, Mu’min (Katalogis, 2013)
This research aimed: 1) to find out community service quality in tha issuing of vehicle (STNK) and vehicle tax (PKB)Â in the samsat Office Palu, 2) to find out restricting factors of that service quality implementation. Qualitative research have to know and describe about Samsat employer to tax obligatory in to go out/sent out STNK and PKB. This research is to have with qualitative where is the data and the information that be collected used work matriks instrument and interview with choosing information, with the research lacation focused to Samsat Office Palu. The result of the research showed that coorperation among employees still less well served. Therefore, factor restricted the service quality of vehicle license (STNK) and vehicle tax (PKB) in the Samsat Office, Palu was service mechanism which inappropriate with service process set in instruction with three ministers.Mechanism, Service Process and Services Quality